2022
DOI: 10.15252/emmm.202115418
|View full text |Cite
|
Sign up to set email alerts
|

Systemically targeted cancer immunotherapy and gene delivery using transmorphic particles

Abstract: Immunotherapy is a powerful tool for cancer treatment, but the pleiotropic nature of cytokines and immunological agents strongly limits clinical translation and safety. To address this unmet need, we designed and characterised a systemically targeted cytokine gene delivery system through transmorphic encapsidation of human recombinant adeno-associated virus DNA using coat proteins from a tumour-targeted bacteriophage (phage). We show that Transmorphic Phage/AAV (TPA) particles provide superior delivery of tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
47
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(50 citation statements)
references
References 81 publications
2
47
0
Order By: Relevance
“…Asavarut and colleagues combined the benefits of phage and rAAV technology to create transmorphic phage/AAV (TPA) particles. These can effectively target tumor cells in vitro and in vivo to deliver immunotherapy genes, while simultaneously having no negative effects on healthy tissues ( 28 ). Kuklik et al developed a bispecific antibody-based gene delivery method in the absence of a new tissue-specific AAV vector, suggesting that redirecting AAVs to particular target receptors are possible ( 29 ).…”
Section: Aav and Aav Vectorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Asavarut and colleagues combined the benefits of phage and rAAV technology to create transmorphic phage/AAV (TPA) particles. These can effectively target tumor cells in vitro and in vivo to deliver immunotherapy genes, while simultaneously having no negative effects on healthy tissues ( 28 ). Kuklik et al developed a bispecific antibody-based gene delivery method in the absence of a new tissue-specific AAV vector, suggesting that redirecting AAVs to particular target receptors are possible ( 29 ).…”
Section: Aav and Aav Vectorsmentioning
confidence: 99%
“…tissues(28). Kuklik et al developed a bispecific antibodybased gene delivery method in the absence of a new tissuespecific AAV vector, suggesting that redirecting AAVs to particular target receptors are possible(29).…”
mentioning
confidence: 99%
“…In this study, we used the recently reported TPA particles characterized by enhanced gene expression, high titer production and large DNA sequence accommodation [9], then constructed the RGD4C.TPA.TNFα (Fig. 1) to evaluate the efficacy of guided systemic delivery of TNF gene for medulloblastoma treatment.…”
Section: Introductionmentioning
confidence: 99%
“…As a tool for targeted and efficient gene delivery, bacteriophage-based vectors have proven their application in prostate and breast cancers, soft tissue sarcomas, gliomas, and pancreatic cancer [10][11][12][13][14] by using a hybrid phage vector, which was previously constructed by incorporating within the phage genome a mammalian transgene expression cassette flanked by inverted terminal repeats (ITRs) from the adeno-associated virus AAV2 [15]. Recently we reported a new generation of phage-based particles for targeted systemic gene delivery consisting of the packaging a recombinant rAAV2 DNA by coat proteins of a filamentous phage, named transmorphic phage/AAV, or TPA [9]. In the TPA particles, the phage genome was removed and an f1 origin of replication is the only remaining phage cis element to allow replication of the single stranded ITR-flanked transgene expression cassette in bacteria and its packaging into the phage capsid provided through infection by a helper phage [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation